Physicochemical and Antimicrobial Properties of Bovine and Salmon Gelatin-Chitosan Films - Matiacevich, S (2013)
The aim was to study thermo-physical and antimicrobial properties of gelatin-chitosan films by gelatin origin (bovine and salmon), chitosan concentration and physical state (glassy or rubbery). Thermo-physical properties (pH, Bloom grade, color, isotherms, glass transition temperature, moisture uptake rate, molecular mobility and film solubility) and antimicrobial effect against Escherichia coli, Salmonella thyphimurium and Listeria monocitogenes were evaluated. The results showed that the presence of chitosan increased the water content of both gelatin films and improved the physical performance of both films, especially for salmon gelatin, without a significant (p0.05) change of color. Antimicrobial activity was effective against all bacteria depending on chitosan concentration and glassy or rubbery state, with the highest effect in glassy state. In conclusion, the evaluated films could be a potential application as bioactive edible films for fresh foods.